(untitled) (Research, Society and Development, 2022)
Rhipicephalus microplus is one of the most important ectoparasites in cattle because it affects animal production and is a vector of bovine babesiosis. Although conventional control of the tick depends mainly on the use of chemical acaricides, the intensive use of these drugs favors the selection of resistant populations. Thus, the objective of this study was to evaluate the in vitro acaricide activity of ethanolic extract (EE) of leaves and crude resin of Protium spruceanum (Benth) in association with a synthetic acaricidal product in two strains of R. microplus using larval package test (LPT) and biocarrapaticidogram test. The qualitative characterization was performed by colorimetric analyses. EE and resin combined with cypermethrin showed efficacy above 90% on R. microplus larvae at concentrations of 50.96 mg ml−1 + 75 μg ml−1 (EE + cypermethrin) and 5.08 mg ml−1 + 15 μg ml−1 (resin + cypermethrin) for both as strains used. High efficacy was not observed in females when the combination was used. However, the values were significantly higher than the efficacy for cypermethrin. The results of phytochemical analysis showed the presence of secondary metabolites of the following classes: phenolic compounds, tannins, alkaloids, terpenes, flavonoids and saponins for EE of P. spruceanum leaves. Only tannins, alkaloids and flavonoids were detected for the crude resin. The association between EE, crude resin and cypermethrin has implications for the control of immature and female stages engendered with R. microplus, which can reduce concentration and cost.